(untitled) (Revista Educação, Artes e Inclusão, 2022)
This experience’s report aims to reflect upon provocations originated in the project “Objects to think about”, through workshops offered to teachers, graduate, and undergraduate students. Writing is presented as a practice report, and it proposes an intertwining between the elements awakened in the participants and the discussions about the relationship between the youngsters and schools in the contemporaneity. The theoretical framework is based on the contributions that encompass the space of the youth in schools (DAYRELL, 2003; 2007) and time-space focusing on studies (LARROSA, 2018). The outcomes, throughout discursive textual analysis (MORAES; GALIAZZI, 2011) constitute themes about the impacts of the Object on the workshop participants and the ways of perceiving the youth times in the school venue, which may limit and restrict students regarding the possibility of distinct creations. Finally, the relevance of discussions whose protagonists are the students is highlighted, with the latter as inhabitants of the school space and, due to it, having a great deal to think and to say about this venue.